NMR Velocity Mapping and RHEO-NMR in Complex Liquids - Eichhoff, U.; Zick, K.; Callaghan, P.T. (Ukrainian Journal of Physics, 2022)
By using the NMR technique, we have determined the velocity distribution and the rate of strain in a micelle solution (cetylpyridinium chloride and sodium salicylate) below and above a critical shear rate and have studied the isotropic and stress-induced ordered nematic phases in a micelle solution CTAB/D2O in a cylindric Couette cell.